IMPROVEMENT OF THE PRACTICE OF SETTLEMENT SERVICES OF FOREIGN TRADE OPERATIONS OF CLIENTS OF COMMERCIAL BANKS - Ibodullaeva Marifat (European Science Publishing, 2025)
Improving the practice of settlement services for clients' foreign trade operations is one of the mandatory conditions for ensuring uninterrupted financing of clients' export and import operations. In particular, the comprehensive use of various types of documentary letters of credit facilitates the timely receipt of export revenue. And the active use of bank guarantees for the quality of exported goods reduces the risk of delivery of low-quality goods. The article identifies current problems related to improving the practice of settlement services for foreign trade operations of clients of commercial banks of Uzbekistan and develops scientific proposals for solving these problems.
Keywords: Commercial bank, export, import, documentary letter of credit, order check, bank guarantee, credit, risk.